FAKTOR-FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA PERBANKAN SYARIAH DI INDONESIA - Damanhur Abbas; Eri Sandi (IAIN Lhokseumawe, 2021)
This study examined the factors influencing the disclosure of corporate social responsibility (CSR) in Islamic banks in Indonesia. This quantitative study used secondary data, and the sampling technique was a non-probability sampling with a purposive sampling method on the research object of Islamic Commercial Banks in Indonesia. The results indicated that the size of the sharia supervisory board did not affect the Corporate Social Responsibility of Islami Banks in Indonesia during 2015-2019, the number of meetings of the sharia supervisory board did not affect the corporate social responsibility of Islamic banks in Indonesia during 2015-2019, and firm size significantly influenced Corporate Social Responsibility of Islamic Banks in Indonesia during 2015-2019, Profitability did not affect the Corporate Social Responsibility of Islamic Banks in Indonesia during 2015-2019, Leverage did not affect on the Corporate Social Responsibility of Islamic Banks in Indonesia during 2015-2019, The size of the Board of Commissioners has no significant effect on the Corporate Social Responsibility of Islamic Commercial Banks in Indonesia for the 2015-2019 period. Simultaneously, the Size of the Sharia Supervisory Board, the Number of Meetings of the Sharia Supervisory Board, Firm Size, Profitability, Leverage, and Board Size. Commissioner significantly influenced Corporate Social Responsibility. The adjusted R-squared value of the independent variables was 93% while the other 7% was explained by other variables outside the regression model.